The Relationship Between Knowledge and Attitude of Adolescent Female Students to Physical Changes During Puberty in Public Secondary School, Bogoro Branch Class, Liquiça District, Timor-Leste - Pereira Ximenes, Imaculada; Jorge Pereira, Santiago; A.O de Oliveira, Felisbela; Seixas da Cruz, Oscar; Anatolia S.M. Exposto, Levi (Rifa'Institute, 2023)
Introduction: Adolescence is a transition in a person’s life that changes from childhood to adulthood. Lack of knowledge of adolescent female students about the physical changes will cause anxiety, fear, shame, different feelings, and confusion. In this case, knowledge is the main component in shaping adolescent attitudes, inadequate knowledge will make adolescents tend to take the wrong attitude. Objective: The purpose of this study is to find out the relationship between the knowledge and attitude of adolescent female students to physical changes during puberty. The research design was a cross-sectional study. Method: The study population was 104 and a sample of 51 adolescent female students was taken using the proportional stratified random sampling technique. Result and Discussion: The results showed that there was a significant relationship between the knowledge of adolescent female students (p-value = 0.012), and attitudes of adolescent female students (p-value = 0.000) to physical changes during puberty. Conclusion: It was concluded that there was a significant relationship between the knowledge and attitudes of adolescent female students to physical changes during puberty.